GTKDynamo: A PyMOL plug-in for QC/MM hybrid potential simulations - Bachega, José Fernando R.; Timmers, Luís Fernando S. M.; Assirati, Lucas; Bachega, Leonardo R.; Field, Martin J.; Wymore, Troy (Journal of computational chemistry, 2013)
Hybrid quantum chemical/molecular mechanical (QCMM) potentials are very powerful tools for molecular simulation. They are especially useful for studying processes in condensed phase systems, such as chemical reactions that involve a relatively localized change in electronic structure and where the surrounding environment contributes to these changes but can be represented with more computationally efficient functional forms. Despite their utility, however, these potentials are not always straightforward to apply since the extent of significant electronic structure changes occurring in the condensed phase process may not be intuitively obvious. To facilitate their use, we have developed an open‐source graphical plug‐in, GTKDynamo that links the PyMOL visualization program and the pDynamo QC/MM simulation library. This article describes the implementation of GTKDynamo and its capabilities and illustrates its application to QC/MM simulations. © 2013 Wiley Periodicals, Inc. This article describes the implementation and the main capabilities of GTKDynamo, a general‐purpose, open‐source graphical interface that combines the molecular modeling program, pDynamo, with the molecular visualizer, PyMOL. The design of the interface places particular emphasis on facilitating the determination of reaction pathways in biological systems using hybrid quantum chemical/molecular mechanical (QC/MM) potentials.